Religious Devotion to Political Secularism - Ghobadzadeh, Naser (Religions, 2022)
By investigating the formation of Twelver Shīʿī theology, this article seeks to show that, despite being political and despite its advocacy of pure theocracy, living in the shadow of a secular state is part of Shīʿī religious doctrine. It is argued that existential threats against Proto-Twelver Shīʿism during its formative centuries led to a messianic conception of the twelfth Imām, the only person whose direct leadership can enable a religiously legitimate state to be formed. Therefore, until his return—which is subject to the will of God—all rulers are usurpers and imposers on the right of the twelfth Imām. Shīʿī leaders are not allowed to seize the institution of government, and non-governmentalism is institutionalized as part of Shīʿī political theology. Instead of focusing on the characteristics of a legitimate ruler and how to form a legitimate government, the founding Shīʿī scholars were concerned with how to co-exist with a usurper. It will be demonstrated that these scholars had differing ideas about the scope and scale of engagement/disengagement with the institution of the state, but none of them discussed the possibility of forming a religiously legitimate government before the return of the twelfth Imām.